Methodology for Assessing the Transport Accessibility of Capital Objects in a Megacity Based on Geoinformation Data - S. V. Mkhitaryan; Zh. B. Musatova; T. V. Murtuzalieva; G. S. Timokhina; I. P. Shirochenskaya (Модернизация, инновация, развитие, 2022)
Purpose: to present the author's methodology and the test results for calculating integral indicators of transport accessibility on the basis of weighted normalized private indicators for three housing estates in Moscow.Methods: the study is based on the application of methods for collecting factual material, its processing, systematic, comparative historical and structural-functional analysis, which were supplemented by multivariate analysis of secondary information using content analysis of existing methods for calculating indicators of transport accessibility of capital objects. The results and conclusions of the research are based on the use of the author's methodology for calculating integral indicators of transport accessibility based on weighted normalized private indicators for three housing estates in Moscow. The analysis of a possible set of criteria for assessing transport accessibility of housing estates in Moscow metropolis was carried out on the basis of the use of a geographic information system database GIS NextGIS QGIS.Results: a review of methodological approaches to the calculation of objective quantitative indicators characterizing the transport accessibility of capital objects is carried out; the author's methodology for calculating the integral indicators of the transport accessibility of residential complexes in Moscow is presented and tested on the basis of weighted normalized private criteria / indicators. The use of the authors’ methodology for calculating integral indicators of transport accessibility based on weighted normalized private criteria / indicators made it possible to calculate the values of indicators of transport accessibility for three housing estates in Moscow, calculate an integrated score for a set of transport accessibility criteria for each housing estate, to give a comparative quantitative assessment of their transport accessibility, to conduct a rating of housing estates in terms of their transport accessibility.Conclusions and Relevance: the presented results of approbation of the author's methodology for calculating the integral indicators of transport accessibility for housing estates in Moscow allow to conduct a comparative and dynamic analysis of housing estates (or larger units) transport accessibility. The results of such an analysis can be applied in order to develop programs for transport infrastructure development of the megacity as a whole, its certain districts and city parts, as well as to assess such programs efciency. The authors see the directions for future research in the defnition and calculation of indicators based on the city dwellers perception of the transport accessibility